Incorporating Spirituality into Graduate Health Professions Education. Issue 4 (7th August 2020) - Espiritu, Elena Wong; TenHaken-Riedel, Joshua P.; Brown, Renee; Frame, Tracy R.; Adam, Jamie; Koch, Allison; Lemmonds, Tamara; Dawson, Alexis; Herrera, Alexa; Jones, Katherine Markley; Myers, Courtney; Owens, Audrey
Abstract: Spirituality is foundational to healthcare practice; therefore, incorporating spirituality into healthcare education is essential to training students to treat the whole person to maximize patient outcomes. However, there is not a singularly agreed-upon definition of spirituality or description of how it should be taught within health profession educational programs. The importance of incorporating spirituality into healthcare education is especially relevant for Christian universities that specifically seek to prepare students to integrate their faith with eventual clinical practice. The purpose of this study was to describe how graduate health profession students (i.e., nursing, occupational therapy, pharmacy, and physical therapy) define spirituality and their vision of spirituality's inclusion in their education. The study used a mixed methods design to survey students in graduate health professions programs and then further refined responses through a focus group. Results indicated most of the participants considered spirituality to be important in their own life; however, there was great variance in the participants' definitions, indicating spirituality is individualized and personal. Participants also agreed that they would be most interested in opportunities including optional mission trips and discussions on how personal spirituality will influence interactions with clients. Although creating educational programing to fit every student's individual definition and needs related to spirituality would be challenging, this study identifies several potential activities that can serve as a starting point for integrating spirituality into healthcare education.